New species of Tinodes from Madagascar (Trichoptera, Psychomyiidae) - Chvojka, Pavel; Gibon, François-Marie (Zootaxa, 2017)
Six new species are described from Madagascar in the genus Tinodes Curtis 1834: Tinodes tafo n. sp., Tinodes ivanovi n. sp., Tinodes helix n. sp., Tinodes furcatus n. sp., Tinodes forcipatus n. sp., and Tinodes marcossi n. sp. Additionally, we provide new distributional data for the species Tinodes schlingeri Johanson & Oláh 2007 and Tinodes dehadawate Johanson & Oláh 2007.